Spirits and sourdough - Cates, Bailey (Cates, Bailey. Magical bakery mystery, 2022)
Katie Lightfoot works at the Honeybee Bakery in Savannah. When a psychic tells Katie that she is being followed by the ghost of a recently murdered woman, Katie knows she must bring the killer to justice.